Pemerataan Akses Pendidikan Sistem Informasi Manajemen pada Lembaga Pendidikan Islam - Ika Merdeka Wati Siregar; Lamsari Lubis (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Equal access to education is a crucial issue in Islamic educational institutions in Indonesia. Ensuring that all students, without exception, have equal access to quality education is vital for the advancement of education in the country. In this context, Management Information Systems (MIS) play a crucial role in enhancing the efficiency, effectiveness, and transparency of educational services. The implementation of MIS can streamline administrative processes, improve decision-making, and facilitate more equitable access to educational resources. This research employs a literature study approach, relying on books and journal articles as primary sources. The findings indicate that the application of MIS provides significant benefits in terms of planning, management, and evaluation. By providing real-time data, MIS enables educational institutions to make better decisions, monitor student progress, and allocate resources more effectively. Additionally, MIS enhances the transparency of educational services, ensuring that all stakeholders—students, parents, and educators—have access to important information related to educational processes and outcomes. However, challenges in the implementation of MIS remain, such as technical barriers related to inadequate infrastructure and limited access to technology, as well as human resource issues like insufficient training. To address these challenges, the research recommends providing comprehensive training programs for educators and administrators, investing in technological infrastructure, and promoting data integration across educational institutions. Overall, while MIS offers many advantages in promoting equal educational access, addressing technical and human resource challenges is crucial to fully realizing its potential in Islamic educational institutions in Indonesia.